A systematic review of population-based dental caries studies among children in Saudi Arabia - Dania Ebrahim Al Agili (Saudi Dental Journal)
Objective: Dental caries critically impacts the health and development of children. Understanding caries experience is an important task for Saudi Arabian policymakers to identify intervention targets and improve oral health. The purpose of this review is to analyze current data to assess the nationwide prevalence and severity of caries in children, to identify gaps in baseline information, and to determine areas for future research. Methods: A search of published and unpublished studies in PubMed, Google, and local Saudi medical and dental journals was conducted for the three keywords “dental,” “caries,” and “Saudi Arabia.” The inclusion criteria required that the articles were population-based studies that assessed the prevalence of dental caries in healthy children attending regular schools using a cross-sectional study design of a random sample. Results/discussion: The review was comprised of one unpublished thesis and 27 published surveys of childhood caries in Saudi Arabia. The earliest study was published in 1988 and the most recent was published in 2010. There is a lack of representative data on the prevalence of dental caries among the whole Saudi Arabian population. The national prevalence of dental caries and its severity in children in Saudi Arabia was estimated to be approximately 80% for the primary dentition with a mean dmft of 5.0 and approximately 70% for children’s permanent dentition with a mean DMFT score of 3.5. The current estimates indicate that the World Health Organization (WHO) 2000 goals are still unmet for Saudi Arabian children. Conclusion: Childhood dental caries is a serious dental public health problem that warrants the immediate attention of the government and the dental profession officials in Saudi Arabia. Baseline data on oral health and a good understanding of dental caries determinants are necessary for setting appropriate oral health goals. Without the ability to describe the current situation, it is not possible to identify whether progress is being made toward these goals. A roadmap with a clear starting point, destination, and pathway is a desperately needed tool to improve the oral health of Saudi Arabian children. Keywords: Oral health, Dental caries, Children, Review, Saudi Arabia